2015
DOI: 10.4103/0971-9784.148322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the International Quality Improvement Collaborative on outcomes after congenital heart surgery: A single center experience in a developing economy

Abstract: Background:The International Quality Improvement Collaborative (IQIC) for Congenital Heart Surgery in Developing Countries was initiated to decrease mortality and major complications after congenital heart surgery in the developing world.Objective:We sought to assess the impact of IQIC on postoperative outcomes after congenital heart surgery at our institution.Methods:The key components of the IQIC program included creation of a robust worldwide database on key outcome measures and nurse education on quality d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…We attribute this result to the active implementation of infection control protocol and hand hygiene culture in our practice in the framework of the International Quality Improvement Collaborative project IQIC. 30,31 We have demonstrated that experiencing complications after paediatric cardiac surgery is an independent risk factor for death and failure-to-rescue is the major contributor for operative mortality in a program with limited systemic resources. Identifying the patterns of perioperative complications, their nature, and significance can provide the valuable material for the development of strategies for their reduction.…”
Section: Discussionmentioning
confidence: 99%
“…We attribute this result to the active implementation of infection control protocol and hand hygiene culture in our practice in the framework of the International Quality Improvement Collaborative project IQIC. 30,31 We have demonstrated that experiencing complications after paediatric cardiac surgery is an independent risk factor for death and failure-to-rescue is the major contributor for operative mortality in a program with limited systemic resources. Identifying the patterns of perioperative complications, their nature, and significance can provide the valuable material for the development of strategies for their reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these issues, some studies have demonstrated that cardiac surgery outcomes in developing countries can be reduced over time through systematic team interventions [18,25]. These interventions are particularly effective in relation to a systems-based approach, standardization, team building, consistent and accurate communication, and active management of changes and quality [26].…”
Section: Plos Onementioning
confidence: 99%
“…International support for congenital cardiac services has evolved beyond the scope of medical missions and exchange programs for training, and now includes successful multinational programs to report clinical outcomes with reference to global benchmarks and to enhance those outcomes using quality improvement practice. 149 As this activity increases, it has also become clear that the Western model of cardiovascular care needs to be modified to provide additional value in social economies in which the healthcare budget is strictly limited. Studies of cardiovascular surgery in low-and middle-income countries highlight the enormous expense both to the system and to patients and their families with use of the technological infrastructure deployed to palliate and repair CHD in the West.…”
Section: Global Burden Of Chdmentioning
confidence: 99%